Effect of Vitamin D replacement in Primary Hyperparathyroidism with concurrent Vitamin D deficiency: a systematic review and meta-analysis - Loh, HH; Lim, LL; Yee, A.; Loh, HS; Vethakkan, SR (National Center for Biotechnology Information Search database, 2017)
INTRODUCTION: We conducted a meta-analysis to assess the effects of vitamin D replacement on biochemical and skeletal parameters in subjects with mild primary hyperparathyroidism (PHPT) and coexistent vitamin D deficiency. EVIDENCE ACQUISITION: A systematic search of all English-language medical literature published from 1980 till May 2016 using Pubmed, Embase and Ovid was performed. Nine observational studies were evaluated after fulfilling the inclusion and exclusion criteria. EVIDENCE SYNTHESIS: A total of 547 patients were examined. All studies used vitamin D2/D3 or calcifediol (25-hydroxyvitamin D3), There was significant improvement of serum 25(OH)D with unchanged serum iPTH level after vitamin D replacement, with pooled d+: 3.10 (95% CI 2.25 to 3.95), p<0.01 and pooled d+: 0.82 (95% CI -0.35 to 1.98), p=0.16 respectively. There was neither worsening of the pre-existing hypercalcaemia [pooled d+: -0.27 (95% CI -1.09 to 0.64, p=0.56) nor hypercalciuria [pooled d+: 3.64 (95% CI -0.55 to 7.83, p=0.09). Two studies assessed in this meta-analysis reported unchanged bone density with vitamin D replacement. CONCLUSIONS: Vitamin D replacement in subjects with mild PHPT and coexistent vitamin D deficiency improved serum 25(OH)D level without worsening of pre-existing hypercalcemia or hypercalciuria. Well-designed multicenter randomized controlled trials examining pre- and post- operative outcomes of vitamin D therapy in patients with different severities of PHPT and vitamin D inadequacy, are warranted to elucidate the most appropriate vitamin D treatment protocol and determine the long-term safety concerns.